Occurrence of Mycobacterium bovis and non-tuberculous mycobacteria (NTM) in raw and pasteurized milk in the northwestern region of Paraná, Brazil - Sgarioni, Sônia Aparecida; Hirata, Rosario Dominguez Crespo; Hiroyuki Hirata, Mario; Leite, Clarice Queico Fujimura [UNESP]; Prince, Karinaandrade De [UNESP]; Leite, Sergio Roberto de Andrade [UNESP]; Vedovello Filho, Dirceu; Siqueira, Vera Lucia Dias; Caleffi-ferracioli, Katiany Rizzieri; Cardoso, Rosilene Fressatti (Sociedade Brasileira de Microbiologia, 2014)
Milk is widely consumed in Brazil and can be the vehicle of agent transmission. In this study, was evaluated the occurrence of Mycobacterium bovis and non-tuberculous mycobacteria (NTM) in raw and pasteurized milk consumed in the northwestern region of Paraná, Brazil. Fifty-two milk samples (20 pasteurized and 32 raw) from dairy farms near the municipality of Maringa, Parana State, Brazil were collected. Milk samples were decontaminated using 5% oxalic acid method and cultured on Lowenstein-Jensen and Stonebrink media at 35 °C and 30 °C, with and without 5-10% CO2. Mycobacteria isolates were identified by morphological features, PCR-Restriction Fragment Length Polymorphism Analysis (PCR-PRA) and Mycolic acids analysis. Thirteen (25%) raw and 2 (4%) pasteurized milk samples were positive for acid fast bacilli growth. Nine different species of NTM were isolated (M. nonchromogenicum, M. peregrinum, M. smegmatis, M. neoaurum, M. fortuitum, M. chelonae, M. flavescens, M. kansasii and M. scrofulaceum). M. bovis was not detected. Raw and pasteurized milk may be considered one source for NTM human infection. The paper reinforces the need for intensification of measures in order to avoid the milk contamination and consequently prevent diseases in the south of Brazil.
Keywords: non-tuberculous mycobacteria; milk; Mycobacterium; PCR-PRA; mycolic acids analysis